Development of New Generation Bone Graft Material: Silver, Silicon Co-Substituted Apatite with Bi-Functional Properties. Issue 1626 (16th January 2014) - Lim, Poon Nian; Chang, Lei; Ho, Bow; Tay, Bee Yen; Cleo, Choong; Thian, Eng San
ABSTRACT: With the rise of ageing population, the need to restore the function of degenerative bone greatly drives the market for bone grafts. Hydroxyapatite (HA) is chemically similar to natural bone mineral and has been widely used in bone graft applications. However, its slow osseointegration process and lack of antibacterial property could lead to implant-related infection, resulting in implant failure. Studies on ionic substitution of apatite have gained attention in recent years with greater understanding of the composition of bone mineral being a multi-substituted apatite. An integrated approach is proposed by co-substituting silver (Ag) and silicon (Si) into HA (Ag, Si-HA) to modify its surface for bi-functional properties. Incorporation of Si can enhance the biomineralization of HA and introduction of Ag can create antibacterial property. Ag, Si-HA containing 0.5 wt.% of Ag and 0.8 wt.% of Si was prepared by a wet precipitation method. A phase-pure apatite with a nanorod morphology of dimensions 60 nm in length and 10 nm in width was synthesized. Surface Ag + ions of Ag, Si-HA were demonstrated to prevent the replication of adherent Staphylococcus aureus bacteria for up to 120 h. Biocompatibility tests revealed that human adipose-derived mesenchymal stem cells (hMSCs) proliferated well on Ag, Si-HA with culturing time. Enhanced cell attachment in turn permitted greater bone differentiation as evidenced in the increase of collagen type I and osteocalcin expressions of hMSCs cultured on Ag, Si-HA as compared to HA from day 14 onwards. Overall, co-substitution of Ag and Si could complement the benefits of each substituent by endowing HA with antibacterial property, and concurrently promoting its biological performance. Their synergistic effects can serve unmet medical needs and solve the problem of implant-related infection. This work also enhances the understanding of substituted apatite with multiple ions for bi-functional properties.